PRICING IN BUYING AND BUYING PLANT SEENDS IN SHARIAH ECONOMIC LAW (STUDY OF BUYING AND BUYING LIME SEEDLINGS IN NAGARI PADANG GANTING) - Daipon, dahyul; Fajri, dion; hendri, hendri; elfiani, elfiani (Al-Amwal : Journal of Islamic Economic Law, 2023)
This journal was written because of the difference in price fixing by lime seed sellers in Nagari Padang Ganting. Where there is a difference in pricing for buyers from within Padang Ganting and buyers outside Padang Ganting. The price difference excludes postage. Based on this, the author wants to know about the pricing carried out by sellers of lime seeds. Then how does the mu'amalah fiqh perspective look at the pricing. This research was conducted in Nagari Padang Ganting. The research method used by the author is a mixed research, namely field research and library research. Field research conducted on sellers, buyers and the local community. And the library research that the writer did used various existing literature in the library that was relevant to the problem to be studied. Research materials were collected through interviews, observation, and documentation. Based on the results of the study, it can be concluded that the price fixing by sellers of lime seeds to buyers from Padang Ganting is the same as the price of one kilogram of lime for one seed. Meanwhile, the price of one seed set for buyers from outside Padang Ganting is more than the price of one kilogram of lime. So there are differences in pricing made by sellers and there are three reasons why sellers differentiate these prices. Firstly, buyers from Padang Ganting are native so prices are lowered. Second, because there is an opportunity to take excess profits from outside buyers. Third, because the seller has been doing this price difference for a long time, so it has become a habit. If seen from the concept of pricing from a mu'amalah fiqh perspective. The difference in pricing by sellers of lime seeds in Nagari Padang Ganting has not fulfilled all the principles of pricing, because there are prices that are not fair for buyers from outside compared to buyers from within Padang Ganting. Then, from a marketing point of view, it has not been fulfilled because the seller is not open in providing information about the price difference. And taking advantage of the ignorance of buyers from outside to gain additional profits, including unjust acts. Because in marketing there are four elements, namely ar-ridha, a healthy comparison of resistance, honesty, justice and openness.Â